Model Determinan Indeks Pembangunan Manusia di Indonesia: Pendekatan Spasial - Santoso, Edy; Wulan Amboro Kasih , Sekar (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2024)
The purpose of this study is to analyze the determinants of the human development index in Eastern Indonesia in 2015-2021 using spatial econometric models used to identify the effect of average years of schooling, life expectancy and pe capita expenditure on HDI in Eastern Indonesia. The results of research on the three models show that the best model for estimating HDI in Eastern Indonesia is the Spatial Durbin Model (SDM) compared to SAR and SEM. The SDM estimation results show that endogenously the three variables have a positive and significant effect on HDI in Eastern Indonesia during the study period. This means that average years of schooling, life expectancy and per capita expenditure are able to encourage an increase in HDI in Eastern Indonesia. While spatially, the HDI variable around the per capita variable alone has an effect but is not significant to the magnitude of HDI in a region. while the average length of schooling and life expectancy of the surrounding area has no effect on the HDI of a region.